RNA Peach and Mango: orthogonal two-color fluorogenic aptamers distinguish nearly identical ligands - Kong, Kristen Y.S. (RNA, 2021)
Two-channel fluorogenic RNA aptamer-based imaging is currently challenging. While we have previously characterized the Mango series of aptamers that bind tightly and specifically to the green fluorophore TO1-Biotin, the next aim was to identify an effective fluorogenic aptamer partner for two-color imaging. A competitive in vitro selection for TO3-Biotin binding aptamers was performed resulting in the Peach I and II aptamers. Remarkably, given that the TO1-Biotin and TO3-Biotin heterocycles differ by only two bridging carbons, these new aptamers exhibit a marked preference for TO3-Biotin binding relative to the iM3 and Mango III A10U aptamers, which preferentially bind TO1-Biotin. Peach I, like Mango I and II, appears to contain a quadruplex core isolated by a GAA^A type tetraloop-like adaptor from its closing stem. Thermal melts of the Peach aptamers reveal that TO3-Biotin binding is cooperative, while TO1-Biotin binding is not, suggesting a unique and currently uncharacterized mode of ligand differentiation. Using only fluorescent measurements, the concentrations of Peach and Mango aptamers could be reliably determined in vitro. The utility of this orthogonal pair provides a possible route to in vivo two-color RNA imaging.